Religious Development: the Role of Village Heads in Increasing Religious Moderation in Gongsol Village - Safira Putri Miranti; Fazira Rahma; Dinda Dian Panjaitan; Alfin Eraninka Sembiring; Sugeng Wanto (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The crisis of religious tolerance in Indonesia is a serious concern for people today. Data shows a decline in the religious harmony index in the country, with issues of religious sensitivity becoming more frequent. This article discusses the important role of village heads in promoting harmony between diverse communities with a focus on the case in Gongsol Village, Karo Regency, North Sumatra. The Gongsol village head implements various programs such as cooperation and elderly gymnastics to strengthen social relations in the village, collaborates with security forces to maintain security, and involves residents in village decision-making. Apart from that, the village head respects the various religions in the village and tries to maintain a balance between religious communities. This article also reviews related literature and the research methodology used.